1996
DOI: 10.1183/09031936.96.09061123
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial deposition and clearance in small airways in asthmatic subjects

Abstract: Asthma tends to impair mucociliary clearance, as assessed from measurements in large airways. However, very little is known about clearance in the smallest airways of the tracheobronchial region.Deposition and clearance was estimated in 11 subjects with stable asymptomatic asthma and 10 healthy subjects after inhalation of 6 µm (aerodynamic diameter) monodisperse Teflon particles labelled with 111 In. The particles were inhaled at an extremely slow flow, 0.05 L·s -1 . Theoretical calculations and experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 21 publications
4
27
0
Order By: Relevance
“…Taken together, aerosol bolus and probe developments have added to the belief that we can now understand and predict particle aerodynamic behaviour within the lungs. They thus support the proposition that we can predictably target test particles onto the bronchiolar airways [9,10].…”
Section: Aerosol Bolus and Probe Techniquessupporting
confidence: 79%
See 3 more Smart Citations
“…Taken together, aerosol bolus and probe developments have added to the belief that we can now understand and predict particle aerodynamic behaviour within the lungs. They thus support the proposition that we can predictably target test particles onto the bronchiolar airways [9,10].…”
Section: Aerosol Bolus and Probe Techniquessupporting
confidence: 79%
“…Transit times through each individual airway unit are then long enough, and yet internal diameters small enough, for many particles to deposit by sedimentation under the influence of gravity. Calculations [9,11] based on WEIBEL model geometry [12] demonstrate the magnitudes of the effects involved.…”
Section: Deposition By Very Slow Inhalationmentioning
confidence: 89%
See 2 more Smart Citations
“…It can be seen (Table 3) that values for the tracheobronchial retention appear to be limited in terms of occurrence and range. An experimentally derived value, from human volunteers, identified that the TR was 47 ± 8% (Svartengren et al, 1996). Unfortunately, this was only done on b 6 μm particles.…”
Section: Resultsmentioning
confidence: 99%